THE TERRITORIAL HERITAGE AS INTEGRATED LOOK OF THE ENVIRONMENT. Analysis of Rosario’s metropolitan waterfront. - Galimberti, Cecilia Inés; Centro Universitario Rosario de Investigaciones Urbanas y Regionales (CURDIUR), (Instituto Carlos Arbeláez Camacho para el patrimonio arquitectónico y urbano, 2016)
This research considers that the partial looks of the heritage fragment and divides the enormous potential of territorial identity that links and unifies. The cultural heritage is a non-renewable resource of the environment, so it intends its revaluation and protection through an integrated reading of the present components in the same one. Across a critical-interpretive analysis is taken as a case study the metropolitan waterfront of Rosario, Argentina, in order to understand the importance of the territorial heritage to be approached as a whole. In order that the protection and valuation of the existing marks are successful, the same ones must be an object of the collective action and be actively compromised with the past of the community as also respond to current needs. Thus, we proposes that the patrimonial interventions in every territory must maintain a perspective that goes beyond geographic jurisdictional boundaries, the temporary ones and the constructed ones for the man, in order to realize attentive actions to the local identity and not with mere purpose of attracting tourism or promoting the gains from the market.